Religious Conflicts and the Future of African Development - Adiele, Okoroafor, Sunday (Religion and Policy Journal, 2025)
Research Problem: Africa’s vast cultural diversity—comprising more than 2,000 languages and over 3,000 ethnic groups—has produced a complex environment where religion often intersects with politics, ethnicity, and economics. This intersection has led to recurring religious conflicts that continue to obstruct development, peace, and social cohesion across the continent. Despite numerous peace initiatives, the persistence of violence indicates that the structural causes of religious conflict, including inequality, institutional weakness, and historical divisions, remain inadequately addressed. Understanding how these underlying factors contribute to instability is crucial for fostering sustainable development in Africa. Research Purposes: This study aims to examine the relationship between religious conflicts and African development through the lens of Structural Conflict Theory. Specifically, it seeks to: (1) identify the structural and socio-economic factors that drive religious violence; (2) analyze the historical and cultural dimensions that sustain conflict; and (3) propose viable strategies for promoting peace, inclusive governance, and socio-economic stability. Research Methods: The research employs a qualitative methodology, integrating insights from historical, sociological, and political analyses. Data are derived from academic literature, policy reports, and documented case studies of major religious conflicts across different African regions. Structural Conflict Theory provides the theoretical framework for understanding how institutional inequalities, power imbalances, and resource competition shape the dynamics of religious confrontation. Results and Discussion: The findings reveal a multilayered relationship between religion and development in Africa. Religious conflict often emerges from deep-rooted structural disparities—such as poverty, ethnic marginalization, and political manipulation of faith identities. Historical legacies of colonialism and uneven resource distribution further exacerbate these tensions. The study demonstrates that the consequences of these conflicts extend beyond spiritual divisions, directly impeding economic growth, education, and governance. However, it also identifies positive trends: interfaith collaboration, grassroots peacebuilding, and regional integration efforts show potential for fostering mutual understanding and stability. Research Implications and Contributions: This study contributes to the expanding scholarship on religion and development in Africa by offering a holistic framework that links structural inequality, conflict, and governance. It underscores the need for inclusive institutions, interfaith harmony, and equitable resource distribution as pathways to sustainable peace. The research recommends strengthening representative governance, mitigating socio-economic disparities, and fostering pan-African and global solidarity to transform religion from a source of division into a catalyst for unity and progress. Ultimately, this study provides valuable insights for policymakers, scholars, and civil society actors seeking to build a peaceful and prosperous Africa grounded in justice, tolerance, and shared development.